Accelerated placental aging mediated the association between prenatal exposure to per- and polyfluoroalkyl substances and small-for-gestational age newborns - Yijun Fan; Liyan Guo; Chang Gao; Yuanyuan Fang; Qiang Zhou; Zhicai Xia; Chengrui Wang; Ruolan Wang; Jia Lv; Lin Tao; Mingliang Fang; Mei Zhao; et al. (Ecotoxicology and Environmental Safety)
Whether prenatal exposure to per- and polyfluoroalkyl substances (PFAS) is a risk factor for small-for-gestational-age (SGA) neonates remain elusive, yet even less is known on the role of premature placental aging in this potential adverse effect. In this analysis of 1046 maternal-infant dyads, 30 legacy and emerging PFAS were measured from maternal serum. Associations between (co-)exposure to PFAS and the incidence of SGA were determined using logistic regression, Bayesian Kernal Machine Regression (BKMR) and quantile-based g-computation (QGC) for single and mixture effect, respectively. Despite the legacy PFAS, prenatal exposure to short-chain emerging PFAS, including perfluorohexane sulfonic acid (PFHxS, per log 10 unit: OR=2.91, 95 %CI=1.63–5.27) and perfluoropentanoic acid (PFPeA, per log 10 unit: OR=3.02, 95 %CI=1.50–6.31) were associated with higher SGA odds. Co-exposure to these highly prevalent PFAS were associated with increased odds of delivering SGA infants, with both models showing emerging PFAS PFHxS and perfluorotridecanoic acid (PFTrDA) being the primary contributors. Further in a 1:2 case-control setting, it was found placental relative telomere length (TL) was shorter in mothers bearing SGA than those with AGA (0.82 vs 0.99, P = 0.001), showing negative association with SGA birth (OR: 0.33, 95 %CI: 0.14–0.76). Mediation analysis revealed that placental TL mediated 17.7 % of the relationship between PFHxS exposure and the risk of SGA birth, respectively. Prenatal PFAS exposure, especially the short-chain congeners, was positively associated with the odds of SGA, and the relationship was partially mediated by shortened placental TL, indicating a need for targeted health management in pregnant mothers at higher risk of SGA due to high PFAS exposure.